Effect of host age, sex and life stage on the prevalence and abundance of sucking lice on Weddell seal in the Antarctic Peninsula - Soto, Florencia Anabella; Negrete, Javier; Klaich, Matias Javier; Leonardi, María Soledad (Anais da Academia Brasileira de Ciências)
Through evolutionary time, seal lice have developed morphological, behavioral, and ecological adaptations to cope with the amphibious lifestyle of their hosts in a co-evolutionary process. Consequently, the dynamics of lice populations are determined by seals behavior. We aim to study the effects of host sex, age class, year, and sampling location, on the prevalence and mean abundance of Antarctophthirus carlinii, on Weddell seals (WS) Leptonychotes wedelli. The study was conducted at two sites in the Antarctic Peninsula, namely, Marambio/Seymour Island (MI) and the Danco Coast (DC). We collected lice from 71 WS: 33 from MI, during the reproductive season, and 38 from DC, during the molting season, between 2014 and 2017. According to our analyses, host age class and sex were the variables that affected prevalence levels of lice on WS. Whereas, age class, year, site, and sex affected lice mean abundance. Juveniles presented higher prevalence and mean abundance than adults, possibly acting as reservoirs for lice as they move through different colonies until they reach reproductive age. Concurrently, seals during molting season were more infested. Unlike nursing, during the molting season seals spend much time ashore forming mixed groups that favor both egg development and lice transmission. Fil: Soto, Florencia Anabella. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Instituto de Biología de Organismos Marinos; Argentina Fil: Negrete, Javier. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo.; Argentina. Ministerio de Relaciones Exteriores y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino. Departamento de Biología de Predadores Tope; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Klaich, Matias Javier. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de la Patagonia "San Juan Bosco"; Argentina Fil: ...